Linear Regression Analysis on Factors Affecting Health Surveillance Personnel Performance in Early Detection of Preeclampsia in Semarang, Central Java - Zella Cahyandaru; Didik Tamtomo; RB Soemanto (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Preeclampsia is a major cause of maternal death both globally and regionally. It can be prevented either through continuous surveillance and early detection activities. City Health Office in Semarang recruited health surveillance officers as an effort to reduce maternal mortality especially due to preeclampsia. The purpose of this study was to analyze factors associated with health surveillance personnel performance in the early detection of preeclampsia.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted in 26 community health centers in Semarang, from October to December 2018. A sample 148 health surveillance personnels was selected by exhaustive sampling. The dependent variable was health surveillance personnels performance. The independent variables were age, work motivation, work stress, job satisfaction, leadership style, and supervision. The data were collected by questionnaire and analyzed by a multiple linear regression.Results: Health surveillance personnel’s performance in early detection of preeclampsia was positively associated with strong work motivation (b= 0.12; 95% CI= 0.07 to 0.16; p<0.001), low work stress (b= 0.08; 95% CI= -0.01 to 0.15; p= 0.058), work satisfaction (b= 0.10; 95% CI= 0.05 to 0.15; p<0.001), leadership style (b= 0.23; 95% CI= 0.10 to 0.37; p= 0.001), and good supervision (b= 0.31; 95% CI= 0.18 to 0.45; p<0.001). Health surveillance personnel’s performance was negatively associated with older age (b= -0.08; 95% CI= -0.16 to 0.01; p= 0.050).Conclusions: Health surveillance personnel performance in early detection of preeclampsia is positively associated with strong work motivation, low work stress, work satisfaction, leadership style, and good supervision. Performance is negatively associated with older age.Keywords: early detection, preeclampsia, performance, health surveillance personnelCorrespondence: Zella Cahyandaru. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: zellacahyandaru@gmail.com. Mobile: +6287832622469.Journal of Health Policy and Management (2019), 4(1): 13-22https://doi.org/10.26911/thejhpm.2019.04.01.02